Short-term effects on heart rate variability of occipito-mastoid suture normalization in healthy subjects - Besson, Cyril; Mur, Thierry; Benaim, Charles; Schmitt, Laurent; Gremeaux, Vincent (Frontiers in Neuroscience, 2023)
Occipito-mastoid structure normalization (OMSN) is an osteopathic manipulative treatment aimed at reducing tension around the jugular foramen, where cranial nerves IX, X and XI exit the skull. The purpose of this study was to observe how heart rate variability (HRV), a marker of autonomic cardiac regulation was modulated after an OMSN versus a sham technique (SHAM). Pre- and post- intervention HRV was analyzed in two randomly chosen groups of 15 participants (OMSN vs. SHAM group). HRV was collected in the supine position 5 min before and 5 min after a 10-minute application of either OMSN or SHAM. Time and group effect was analyzed using a two-way ANOVA. Independently from group intervention, a significant time effect induced increased HRV. No group effect differences were observed. Multiple comparisons for time and group interaction showed that the root mean square of successive differences (RMSSD), a vagally-mediated HRV variable, increased to a greater extent for OMSN group (p=0.03) than for the SHAM group. However, both OMSN and SHAM techniques had a significant effect upon HRV. Compared to a SHAM technique, OMSN had a significant effect on HRV vagally-related metric RMSSD in the short term. We conclude that ten minutes of OMSN may be used to induce a short-term influence on parasympathetic autonomic nervous system modulations.